Layanan Bimbingan Konseling Dalam Peningkatan Motivasi Belajar Siswa SMA N 1 Kota Metro - Hanwar Priyo Handoko (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2020)
BK in Improving Student Learning Motivation at SMA N 1 Kota Metro, the types of services are: Information services. School principals and BK teachers have implemented these services, such as: information about knowledge about their environment, learning resources, and information on continuing studies so that students can make it easier to make plans to enter the University; Placement and distribution services, in this case the Principal and BK teacher have assisted students in developing the potential students have, it can be seen from the collaboration between extracurricular teachers and BK teachers in developing student potential. Individual counseling services, school principals and school counselors always help students if students experience problems, school principals and school counselors work together with parents to deal with difficulties, are lazy in learning, by asking students questions and providing solutions.